The evolution of the insurance system from idea to law - Bensalhia, Saber; Chaoua, Mehdi (Journal of Human Sciences, 2022)
Insurance is part of several civilizations, in particular that which is based on cooperation and solidarity between individuals to face a certain risk and share the losses resulting from its realization. Man has long tried to avoid the continuous dangers to which it is exposed, so it has tried to use preventive means to ensure safety and security to deal with the consequences of potential dangers that afflict it, and therefore it is difficult to attribute insurance to a civilization particular, because the idea of ​​insurance developed in stages and through historic stations, until it was embodied in legal texts to regulate and secure many sectors.